2018
DOI: 10.1088/2040-8986/aadea9
|View full text |Cite
|
Sign up to set email alerts
|

Phase shifter with adjustable resolution for phase-shifting interferometry

Abstract: This paper presents a simple and practical phase shifter able to adjust its resolution in a wide range for phase-shifting interferometry. This proposal is carried out in a double-aperture common-path interferometer, placing at the input plane an additional grating in each aperture. We demonstrate that when both gratings are rotated at the same angle, the resolution of phase-step improves considerably without the need of using a sophisticated system of high quality. This method is verified with numerical simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…where the spatial dependencies in the optical fields have been omitted for the sake of convenience, n is a natural number that keeps relation with the grating diffraction orders and with the separation of the entrance apertures, in other words, s 0 = λf ξp n, known as the matched condition for interference [30,33]. The use of this matched condition allows to interfere the order m of E r with the order m + n of E p , whose intensity by substituting equations ( 4)-( 6) into equation ( 7) is possible to be expressed by…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where the spatial dependencies in the optical fields have been omitted for the sake of convenience, n is a natural number that keeps relation with the grating diffraction orders and with the separation of the entrance apertures, in other words, s 0 = λf ξp n, known as the matched condition for interference [30,33]. The use of this matched condition allows to interfere the order m of E r with the order m + n of E p , whose intensity by substituting equations ( 4)-( 6) into equation ( 7) is possible to be expressed by…”
Section: Mathematical Modelmentioning
confidence: 99%
“…To reduce this uncertainty, they propose to place two gratings with a larger period at the input plane, with which the matched condition is not affected; and demonstrated that their relative position introduces a phase step, in such a way that, with only one movement, a phase step is obtained with a lower uncertainty. Recently in 2018 [33], it was theoretically demonstrated that the uncertainty decreases with the polar rotation of both gratings. However, in this last proposal, the system uncertainty was not provided, and the experimental validation was not enough.…”
Section: Introductionmentioning
confidence: 99%
“…As is known [33,[35][36][37][38], a DACPI consists of two lenses, L 1 and L 2 , separated by a distance 2f, where f is the focal distance of both lenses; the DACPI containing three planes. In the first place, the input plane contains two apertures, w H and w V , separated vertically by a y 0 distance.…”
Section: Phase Modulationmentioning
confidence: 99%
“…The setup is based on a doubleaperture common-path interferometer (DACPI) in whose input plane is placed two modulated Ronchi ruling and two orthogonal polarizers in order to separate the polarization components. The setup is more stable than a standard twoarm interferometer, and the optical path difference is easily calibrated by transversal or rotational displacements of the gratings [33]. Another critical point in the polarization conversion by interferometric techniques is the creation of the spatial phase-shifting.…”
Section: Introductionmentioning
confidence: 99%
“…In the optical coherence tomography imaging system, to obtain the tomographic image of the measured object, the optical path of one arm in the interferometer needs to be adjusted to realize interference patterns. The phase-shifting interferometry technology, , as a new imaging and measurement technology, and different phase shifts on the interferometric reference arm are required to generate interference patterns with corresponding different phase shifts on the recording plane. In communication systems, electro-optic modulators , modulate the optical phase of light to achieve signal transmission.…”
Section: Introductionmentioning
confidence: 99%